Rational monomer design for the synthesis of conjugated polymers by direct heteroarylation polymerization - Kakde, Navnath R.; Sharma, Himanshu; Dalvi, Nitin V.; Vanka, Kumar; Asha, S. K (ACS Polymers Au, 2024)
This study focuses on the design concepts that contribute to the C–H activation in bithiophene-flanked monomers incorporating naphthalene diimide (NDI), perylene diimide (PDI), and fluorene (FLU) and their polymerization by direct heteroarylation. Density functional theory (DFT) calculations reveal distinct energy requirements for C–H bond abstraction, which is dictated by the electron-withdrawing strength of the central aromatic core flanked by bithiophene. These provide insights into the reactivity of each monomer for C–H bond activation. Proton NMR spectroscopic experimental results confirm the favorable energetic profiles predicted by DFT, with NDI- and PDI-flanked monomers exhibiting lower energy requirements than fluorene-flanked monomers. Successful polymer synthesis is demonstrated for NDI and PDI, while the fluorene-flanked monomer shows challenges due to its higher energy demands.